2008
DOI: 10.1111/j.1471-4159.2008.05487.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of neuron‐restrictive silencing factor in the specific expression of cocaine‐ and amphetamine‐regulated transcript gene

Abstract: 1These authors contributed equally to this work.Abbreviations used: CART, cocaine-and amphetamine-regulated transcript; ChIP, chromatin immunoprecipitation assay; FBS, fetal bovine serum; HDAC, histone deacetylase; INS-1, insulin-secreting cells; NRSE, neuron-restrictive silencer element; NRSF, neuron-restrictive silencer factor; PC12, pheochromocytoma cells; REST, repressor element-1 silencing transcription factor; shNRSF, short hairpin RNA for NRSF; TSA, trichostatin A. AbstractCocaine-and amphetamine-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…By contrast, little is known about the repression mechanism. This study together, with our previous findings (25), identified a dual NRSE mechanism for CART repression. As far as we know, this is the first evidence to systematically reveal the repression mechanism of CART transcription.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…By contrast, little is known about the repression mechanism. This study together, with our previous findings (25), identified a dual NRSE mechanism for CART repression. As far as we know, this is the first evidence to systematically reveal the repression mechanism of CART transcription.…”
Section: Discussionsupporting
confidence: 87%
“…The cloned reporter gene vector containing the proximal promoter region of the CART gene (Ϫ700 to ϩ39 bp; P-Luc) was a kind gift from Dr. Peter Morgan (19). The reporter gene construct containing the truncated CART promoter (Ϫ700 to ϩ12 bp) without the NRSE sequence (tP-Luc) was described previously (25). The CART intron I region fragment was generated by PCR amplification using genomic DNA from human mesenchymal stem cells as the template, and primers were as follows: sense, 5Ј-GGATCCTGCTGATGCT-ACCTCTG-3Ј; antisense, 5Ј-GTCGACGCCATACTTCTTC-TCATAG-3Ј.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations